Personal files and creative process documents: a necessary overlap - Costa, Rosa da Penha Ferreira da (Farol, 2024)
It presents concepts about personal archives, their relationship with archival science, and the creation process documents in the context of artists’ personal archives. Its objectives are: to define personal files, address personal files in the context of archival science, provide examples of personal files in some areas of knowledge, discuss the relevance of personal files in the context of creation process documents. This is a bibliographical research. It concludes that personal archives are fundamental for research and preservation of memory.